2002
DOI: 10.1161/01.str.0000034788.70971.14
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Treatment of Ruptured Intracranial Aneurysms in Patients Aged 65 Years and Older

Abstract: Background and Purpose-We sought to describe the clinical outcome and results obtained in the endovascular therapy of ruptured cerebral aneurysms in the elderly over an 8-year period. We compared endovascular therapy results in patients aged Ն65 and Ͻ65 years. Methods-During

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
44
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(49 citation statements)
references
References 29 publications
3
44
1
1
Order By: Relevance
“…26 The outcomes in single-center series were highly dependent on condition at presentation, with Hunt and Hess grades 1 and 2 leading to good outcomes in 57%-94%, and Hunt and Hess grades 4 and 5 leading to favorable outcome in 0%-16%. [9][10][11][12][13]15 It is impossible to know the condition at presentation of the patients in the NIS, but it is quite likely that many of the bad outcomes in the NIS patients were due to the severity of the initial hemorrhage. A subgroup analysis of patients 65 years and older enrolled in ISAT showed that 60.1% of patients allocated to coiling were independent compared with 56% allocated to clipping (P ϭ .47).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…26 The outcomes in single-center series were highly dependent on condition at presentation, with Hunt and Hess grades 1 and 2 leading to good outcomes in 57%-94%, and Hunt and Hess grades 4 and 5 leading to favorable outcome in 0%-16%. [9][10][11][12][13]15 It is impossible to know the condition at presentation of the patients in the NIS, but it is quite likely that many of the bad outcomes in the NIS patients were due to the severity of the initial hemorrhage. A subgroup analysis of patients 65 years and older enrolled in ISAT showed that 60.1% of patients allocated to coiling were independent compared with 56% allocated to clipping (P ϭ .47).…”
Section: Discussionmentioning
confidence: 99%
“…The risk of poor outcome after aneurysmal SAH increases with advancing age, 9 and a less invasive treatment with endovascular coil embolization rather than clipping has been advocated in the elderly. [9][10][11][12][13][14][15] Although the potential benefits of a less invasive treatment in elderly patients with aneurysmal SAH may seem intuitive, 16 some series have shown that the risks of endovascular coil embolization in this age group are not negligible, 17 and 1 singlecenter study demonstrated that the introduction of coil embolization of ruptured aneurysms was not associated with improved outcomes in elderly patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Procedural morbidity has also been decreasing. 14,15,[19][20][21][23][24][25] In addition, unlike open surgery, endovascular morbidity and mortality seem to be less dependent on a patient's age. 11,31,34 Our series demonstrated that endovascular coiling of elderly patients with unruptured intracranial aneurysms is safe and effective.…”
Section: Discussionmentioning
confidence: 99%
“…Endovascular coiling has allowed us to treat more patients, including elderly individuals, in whom surgical clipping is considered risky. [19][20][21][22][23][24][25] Nevertheless, few studies 26 assessing the results of endovascular treatment for unruptured intracranial aneurysms in elderly patients have been undertaken, and optimal management of patients with unruptured intracranial aneurysms and the feasibility and the effectiveness of embolization are yet to be determined. We present our single-center experience of endovascular treatment in patients 70 years of age and older.…”
mentioning
confidence: 99%